Study of Consumer Behavior on TikTok: Motivations, Preferences, and their Impact on Marketing Trends - Safrianto, Arief Syah; Herawati, Heny; Fauzan, Rusydi (Journal of Management, 2024)
This study seeks to investigate the impact of fashion content, content inventiveness, and user interaction on consumer behavior, as well as the moderating role of consumer motivation in enhancing these interactions. Data was obtained from active social media users who were exposed to fashion content. Statistical tests were used in the analysis, as well as Moderated Regression Analysis (MRA). The study found that fashion content (X1) had a significant positive impact on customer behavior (Y), with a significance value of 0.000 (p < 0.05). Content inventiveness (X2) has a considerable beneficial impact on consumer behavior (Y) with a significance level of 0.000 (p < 0.05). Furthermore, user interaction (X3) has a considerable beneficial impact on customer behavior (Y) with a significance value of 0.000 (p < 0.05). Furthermore, the MRA results suggest that consumer motivation (M1) moderates the effect of fashion content on customer behavior, with a p-value of 0.01. Customer motivation, with a significance value of 0.00, likewise moderates the effect of content innovation on customer behavior, as does user interaction. Thus, consumer motivation enhances the link between the independent factors (fashion content, content creativity, and user engagement) and the dependent variable (consumer behavior).This study emphasizes the importance of customer motivation in enhancing the efficiency of marketing tactics using fashion content on social media. The findings have practical implications for marketers and content providers in the fashion sector to pay more attention to customer motivation factors in order to promote favorable consumer behavior toward their brands.